2021
DOI: 10.1002/elps.202000356
|View full text |Cite
|
Sign up to set email alerts
|

Detection of nucleotides in hydrated ssDNA via 2D h‐BN nanopore with ionic‐liquid/salt–water interface

Abstract: Accomplishing slow translocation speed with high sensitivity has been the most critical mission for solid‐state nanopore (SSN) device to electrically detect nucleobases in ssDNA. In this study, a method to detect nucleobases of ssDNA using a 2D SSN is introduced by considerably reducing the translocation speed and effectively increasing its sensitivity. The ultra‐thin titanium dioxide coated hexagonal boron nitride nanopore was fabricated, along with an ionic‐liquid 1‐butyl‐3‐methylimidazolium hexafluorophosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…The h-BN nanopore fabrication processes are outlined in our previous work, , and the nanopores in Si x N y purchased from Norcada (NBPX5001Z-HR, nominally ∼12 nm thick) were fabricated using CDB and CT-CDB . dsDNA (10787018, Fisher Scientific) was used as supplied, and the stock solutions of hSTf (T0665, Sigma-Aldrich, USA) were prepared by dissolving the as-supplied solid in >18 MΩ cm ultra-pure water (ARS-102 Aries high-purity water systems).…”
Section: Methodsmentioning
confidence: 99%
“…The h-BN nanopore fabrication processes are outlined in our previous work, , and the nanopores in Si x N y purchased from Norcada (NBPX5001Z-HR, nominally ∼12 nm thick) were fabricated using CDB and CT-CDB . dsDNA (10787018, Fisher Scientific) was used as supplied, and the stock solutions of hSTf (T0665, Sigma-Aldrich, USA) were prepared by dissolving the as-supplied solid in >18 MΩ cm ultra-pure water (ARS-102 Aries high-purity water systems).…”
Section: Methodsmentioning
confidence: 99%
“…Subsequently, they were able to differentiate between all four types of 30-mer DNA homopolymers and single nucleotides by using a 2.8 nm diameter MoS 2 pore. Similarly, a viscosity gradient was proposed to considerably reduce the translocation speed of ssDNA across h -BN nanopores and, meanwhile, increase the sensitivity of nanopore detection by adding 3% of pure water to the highly viscous ionic liquids . Liang et al .…”
Section: Challenges To Achieving Dna Sequencingmentioning
confidence: 99%
“…Similarly, a viscosity gradient was proposed to considerably reduce the translocation speed of ssDNA across h-BN nanopores and, meanwhile, increase the sensitivity of nanopore detection by adding 3% of pure water to the highly viscous ionic liquids. 142 Liang et al predicted via MD simulations that applying a lower voltage or decreasing pore size also resulted in slower DNA translocation through a MoS 2 pore. 143 Aside from the aforesaid general strategies, a few alternative methods possibly specific to 2D materials were also proposed for reducing DNA speed and, more importantly, moving DNA bases across the pore one base at a time.…”
Section: Challenges To Achieving Dna Sequencingmentioning
confidence: 99%
“…FEB/FIB is the most common technique to drill nanopore on a suspended film directly. A large variety of materials including SiN [9,30,31,[64][65][66][67][68][69][70][71][72][73], SiO 2 [80] and 2D materials [40,83,84,86,88,108] are used for the formation of nanopores in different sizes. Li et al [47] reported an ion beam sculpting technique to fabricate 1.8 nm nanopore in a free-standing SiN membrane supported on Si substrate.…”
Section: Feb/fib Drillingmentioning
confidence: 99%